Can the Ratio SUVmax of the Lesion/SUVmax of Mediastinal Tissues Guide the Choice of Surgical Access for the Resection of Thymic Epithelial Tumors? - Moraitis, Sotirios D.; Agrafiotis, Apostolos C.; Skoura, Evangelia; Kalkanis, Dimitrios; Moraitis, Dimitrios; Tomos, Periklis; Liakakos, Theodoros; Angouras, Dimitrios (Frontiers in Surgery, 2022)
Background: There are studies showing the utility of the 18-fluorodeoxyglucose positron emission tomography scan in the management of patients with thymic epithelial tumors. It seems to be a correlation between the Standard Uptake Value (SUVmax) of thymic epithelial tumors and the histological type and the stage. This study aims to use the ratio of the SUVmax of the lesion to the SUVmax of the adjacent mediastinal tissues in order to guide the choice of the surgical access. Methods: All patients that presented an anterior mediastinal lesion with a high suspicion of being of thymic origin were included in a prospective database. A ratio inferior to 1 could predict a benign nature and less aggressive behavior and a minimally invasive approach was performed. A ratio superior to 1 suggested a malignant and aggressive behavior and a median sternotomy (or a thoracotomy) was performed. Results: There were 15 male (mean age 44.6 years, range 25-73) and 15 female patients (mean age 50.1 years, range 25-76). When the ratio is inferior to 1, it predicts benign disease in 80% of cases. When it is superior to 1, it predicts in half of cases advanced histological types (high risk thymomas and thymic carcinomas). On the contrary, it can quite accurately predict advanced Masaoka-Koga stages. Conclusions: The protocol of this study is in accordance with the current literature showing the utility of 18-fluorodeoxyglucose positron emission tomography scan in the treatment of thymic epithelial tumors. This study goes one step further since the choice of surgical access is based on the SUVmax values. The ratio SUVmax of the lesion/SUVmax of the mediastinal tissues could be a new marker, more pertinent than absolute SUVmax values.